2020
DOI: 10.18203/2320-6012.ijrms20204882
|View full text |Cite
|
Sign up to set email alerts
|

The role of peritumoural brain edema in ascertaining the high risk meningiomas

Abstract: Background: Meningiomas are benign tumours which possess a potential to recur. Peritumoural brain edema (PTBE) has been associated with several complications and future recurrence. This study aims to establish the relation of PTBE in different histopathological grades and subtypes of meningiomas and in addition determines the significance of PTBE in ascertaining tumour recurrence.  Methods: Complete surgical resection samples from 50 meningioma patients were obtained from the neurosurgical department and histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Many studies have showed that PTBE was significantly associated with recurrence in meningiomas [22,23]. Furthermore, sphenoid ridge and parasagittal meningiomas, represented the most common locations for recurrent in one study, and both of them had preoperative PTBE in all cases [24].…”
Section: Discussionmentioning
confidence: 79%
“…Many studies have showed that PTBE was significantly associated with recurrence in meningiomas [22,23]. Furthermore, sphenoid ridge and parasagittal meningiomas, represented the most common locations for recurrent in one study, and both of them had preoperative PTBE in all cases [24].…”
Section: Discussionmentioning
confidence: 79%
“…Grading based on histopathology has shown limitations in determining the disease prognosis as not only grade II and III meningiomas but a group of grade I meningiomas have also shown recurrence following surgery and subsequent resistance to radiotherapy. This has therefore demanded for the need of immunohistochemical markers which can ascertain tumor prognosis [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%